Comparative analysis of the structure and biodiversity of a coastal sabinar and its sucession in the Espacio Natural Doñana - Cámara Artigas, Rafael; Alonso García, José Ramón (Geographicalia, 2015)
The purpose of this work, consisted in the analysis and comparison of the structure, composition and biodiversity of the Coastal Phoenicean juniper and its Scrub Succession, throughout structure diagrams, importance value and both parametrical/no parametrical biodiversity alpha indexes. These species can be found in the Natural Space of Doñana, located at the southwest of Spain, specifically at Medano del Asperillo. This analysis, allows to establish the diachronically rhythm, structure, composition and biodiversity changes between both plant communities: The scrub monte blanco, based upon the deforested area since 1947 and a sample of the Sabinar taken from las Artaranzas of the same year.
Keywords: Phoenicean juniper; Doñana; monte blanco; alpha biodiversity